Earth and Sky: Architectures of Melluso in the Mediterranean Landscape - Antonio Biancucci (Agathón, 2017)
By the occasion of the recent exhibition on the architecture in Palermo 'Tra terra e cielo' on Vincenzo Melluso, the author tells, through the photography of Giovanni Chiaramonte, of two buildings that interpret the Apulian territory and define the Mediterranean landscape, interacting with each other at completely different dimensions: a reflection on the relationship between architecture and landscape.